Impact of two different strength/conditioning training interventions on sport and strength performance of junior male judokas - Osipov, A.; Guralev, V.; Iermakov, S.; Ratmanskaya, T.; Galimova, A.; Kudryavtsev, M. (Physical Activity Review, 2022)
The influence of different strength training interventions on strength and competitive performance has been insufficiently examined in elite junior judokas. This study aimed to investigate the impact of different strength interventions in precompetitive training process of elite junior male judokas. Material and Methods. Fifty-three elite judokas (age: 17.22±1.37 yrs, height: 176.34±5.47 cm, body weight: 78.46±6.22 kg, judo training experience: 4.52±0.89 years) performed two different 8-week strength training interventions. Group 1 (n=27) were performed "strength" intervention, group 2 (n=26) were performed "CrossFit®" intervention about 5.3-6.0 hours per week. The base training exercises were as follows: bench press, barbell bench pull and lat pull-down, clean & jerk, snatch, squats and knee flexion curl, pull up. The handgrip strength test, the one-repetition maximum tests, pull up test and competitive performance evalution, were in this study. Results. In post-intervention period, were found that bench press and back squat findings were significantly (p=0.05) higher in judokas (group 1) as compared to judokas (group 2). There were significantly (p=0.05) higher pull up findings in judokas (group 2). No significant differences were observed among the groups with regard to competitive performance values within 3.5 months after post-intervention. Conclusions. This study demonstrated that 8-week of different strength training interventions are not equally effective to increase performance of junior male judokas in specific strength tests and not to change competitive performance of athletes within 3.5 months after strength intervention. The final decision for the particular strength training intervention ("strength" or "CrossFit®") can be decided according to an judoka's individual challenges during the competitive season.